IMPROVING POSYANDU CADRE CAPABILITIES FOR STUNTING PREVENTION THROUGH PARENTING TRAINING AND MENTORING PROGRAMS - Sri Usodoningtyas Arselan; Mamduh Winangun; Dindy Sinta Megasari; Mutimmatul Faidah; Novia Restu Windayani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tunas Pembangunan Surakarta, 2026)
Stunting remains a chronic nutritional problem in Indonesia, influenced by inappropriate parenting practices, low nutritional literacy, and limited access to and utilization of health services. This community service program aims to improve the capabilities of integrated health post (Posyandu) cadres regarding parenting practices for toddlers in the context of stunting prevention, measured by training effectiveness through pre-test and post-test evaluations. This activity uses a descriptive and participatory approach, with systematic stages ranging from preparation, core implementation, and evaluation. The results show that most cadres are late adults and have more than five years of experience in Posyandu services, as well as a high school education, which are important assets in absorbing the training material. Pre-test and post-test evaluations showed an increase in comprehension scores from 83% to 100%. This indicates that the designed training is effective in strengthening the capabilities of Posyandu cadres as the frontline in stunting prevention. This program emphasizes the importance of ongoing training to equip cadres with knowledge and skills appropriate to the challenges in the field. Keywords: Stunting Prevention, Integrated Health Post Cadres, Toddler Parenting Patterns